基于小波—Hilbert解调的齿轮故障诊断方法 - 崔颖; 赵军; 孔明 (Jixie chuandong)
A method of gear fault feature extraction based on wavelet transform and Hilbert demodulation is proposed.On the basis of fault mechanism and characteristic frequencies of gearbox fault,wavelet transform is used to decompose the vibration acceleration signals of gear faults into different frequency bands,thus realizing the extraction of nonlinear coupling characteristic frequency of gear fault,which is then used to achieve accurate fault information by Hilbert demodulation.The result shows that the proposed method can effectively improve the frequency resolution and realize accurate extraction of fault feature,and it has certain practical value for the gear fault diagnosis of automobile gearbox when applied to the automotive industry.